Sistem Pendukung Keputusan Dengan Menggunakan Metode ELECTRE II Dalam Menentukan Faktor Yang Mempengaruhi Pemilihan Sabun Mandi - Fazariani, Nabila; Sari, Rina Filia; Aprilia, Rima (Universitas Negeri Gorontalo, 2024)
Reviewed and with the increasing public awareness of skin health, soap manufacturers are competing to offer their products with various fragrances, forms, and benefits to the public. Each individual certainly has different criteria in choosing bath soap products, such as packaging, product price, product fragrance, type and form, and so on. The purpose of this research is to determine the factors that serve as the basis for each individual in choosing bath soap products by implementing the Elimination et Choix Traduisant la RÃ©alitÃ© II (ELECTRE II) method. The ELECTRE II method uses simple criteria, namely setting the same threshold value for all criteria. In contrast, other methods use pseudo criteria where the threshold value is not the same for all criteria. The ELECTRE II method is one of the Multi-Attribute Decision Making (MADM) methods that is effective in determining ranking, as it involves both qualitative and quantitative criteria. Based on the research results, product quality becomes the priority factor in choosing bath soap products, with a Concordance value of 1.375 and a Discordance value of -1.80063, as well as the highest average rank, which is 1. The product price factor ranks second, followed by the skin condition factor in third place, and the product fragrance factor, which ranks last with an average rank of 4.